2008
DOI: 10.1002/mop.23378
|View full text |Cite
|
Sign up to set email alerts
|

Design of a compact CPW‐fed UHF RFID tag antenna for metallic objects

Abstract: number of right-hand sides to be solved for the complete monostatic RCS calculation is 91 for each example. It can be seen that the number of MVPs of the SAI-GMRES method varies largely with respect to incident angles (i.e., right-hand sides), while that of the GMRESE methods are more similar and almost constant for each example. This is another advantage of the GMRESE method proposed in this article. More detailed comparisons can be found in Table 5, in which the cumulated number of matrix-vector products and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…2(a), it is seen that a resonant mode near 910 MHz band can be excited with good matching to the input impedance of the IC microchip. For the realization of impedance matching between the tag antenna and IC chip, the half-power (3 dB return loss) bandwidth specification had been adopted in the proposed designs [1,8]. From the related results shown in Fig.…”
Section: Antenna Designmentioning
confidence: 99%
“…2(a), it is seen that a resonant mode near 910 MHz band can be excited with good matching to the input impedance of the IC microchip. For the realization of impedance matching between the tag antenna and IC chip, the half-power (3 dB return loss) bandwidth specification had been adopted in the proposed designs [1,8]. From the related results shown in Fig.…”
Section: Antenna Designmentioning
confidence: 99%
“…Therefore, it is found that a new matching mode close to the fundamental matching mode of the regular F-shaped dipole antenna is obtained to enhance the operating bandwidth for RFID UHF band. For the realization of impedance matching between the tag antenna and IC chip, the half-power (3 dB return loss) bandwidth specification had been adopted in the proposed designs [3,9]. From the experimental results, the measured bandwidth .…”
Section: As Shown Inmentioning
confidence: 99%
“…The detection range and accuracy are directly dependent on the performance of reader/tag antennas. Some tag antennas for UHF RFID system have been proposed using planar unsymmetrical antenna [2], symmetrical dipole antenna [3][4][5][6], meander antenna [7] and slit antenna mounted on metal materials [8,9]. However, tag antenna applied for the glass object of the car is very scant in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…However, the above presented designs need larger dimensions and are unable to meet the dimensional considerations of the product. Moreover, the half-power matching bandwidth of the above tag designs cannot meet the specification of the UHF band (860-960 MHz) [4,6]. In this Letter, a compact UHF tag antenna with bandwidth enhancement is proposed.…”
mentioning
confidence: 98%
“…However, there are some problems to be overcome for UHF label tags attached to the surface of metallic objects owing to electromagnetic wave scattering from the metal plane. Some metal tag antennas have been presented by using PIFA structures [1,2], dipole antennas [3], slit structures [4][5][6] and T-matching networks [7]. However, the above presented designs need larger dimensions and are unable to meet the dimensional considerations of the product.…”
mentioning
confidence: 98%